Impact of climate change on adipose-derived stem cells: A molecular and histological study - Saeed Motesaddi Zarandi; Rasoul Yarahmadi; Rasul Nasiri; Mohammad Bayat; Hossein Nasiri; Abdollah Amini; Mohammad Esmaeil Motlagh; Hassan Rasoulzadeh (The Journal of Climate Change and Health)
Background: Climate change, particularly temperature and humidity fluctuations, can affect biological systems. This study specifically investigates the impact of these two key aspects of climate change on adipose-derived stem cells (ADSCs) as a pilot study and starting point for further examinations into the biological effects of climate change-associated conditions. Methods: One-month-old male rats were kept for 4 months (equal to a 10-year climatic period) in 4 groups and exposed to conditions based on climatic data from Tehran's synoptic stations. Rats in the control group were exposed to conditions based on climatic data from 1991, and groups 2–4 were exposed to conditions based on climatic data from 1991 to 2000, 2001–2010, and 2011–2020, respectively. Monthly temperature, humidity, and day/night cycle averages were selected for animal exposure. After exposure, fat-derived stem cells were taken from each subject and assays assessing reactive oxygen species (ROS), cell viability and proliferation, and apoptosis were performed. Results: From 1991 to 2020, Tehran experienced an average temperature increase of 1.5 °C and a 15 % decrease in average humidity, conditions which when replicated in rodent models were associated with increased rates of ROS and caspase-3 expression, a reduction in Ki-67 antigen expression and in the duration of the life of cells, and an increase in the rate of apoptosis, such that apoptosis in ADSCs reached 25.51 %. Conclusion: The study demonstrates that environmental conditions similar to those from climate change are associated with significant changes in ADSCs and emphasizes the need for further research to understand their impact on health.